PERBANDINGAN NILAI EKSPANSIF TANAH BERDASARKAN HASIL INDEX PROPERTIES DAN 1-D FREE SWELL TEST - Tarisa Pironika; Ely Mulyati (Ensiklopedia of Journal, 2025)
Expansive soil is a type of soil that is susceptible to significant volume changes due to fluctuations in water content. This study aims to analyze the comparison of the expansive soil values based on the Index Properties results and the 1-D Free Swell Test with variations in bentonite mixture of 0%, 30%, 40%, 50%, 60%, and 100%. The observed parameters include the liquid limit (LL), plasticity index (PI), and the expansion value from the 1-D Free Swell Test. The test results show that the addition of bentonite significantly increases the plasticity of the soil. The LL value increased from 56.37% at 0% bentonite to 114.33% at 100% bentonite, while the PI value increased from 34.77% to 92.72%. Based on classification, soil with a bentonite mixture ≥30% is categorized as very high. Meanwhile, the results of the 1-D Free Swell Test show a relatively small expansion variation, namely 2.91%–3.76%, with a classification of low to medium expansion potential.Effective Index Properties are used as an early indicator for the identification of expansive soil, while the 1-D Free Swell Test is more representative in describing the actual development potential in the field.Keywords: expansive soil, bentonite, index properties, free swell test